Development of Multi-Coils Circular Eddy Current Sensor for Characterization of Fibers Orientation and Defect Detection in Multidirectional CFRP Material, ISSN / e-ISSN 0934-9847 / 1432-2110 - Benhadda Nabil; Hachi Dahmane; Helifa Bachir; Lefkaier Ibn Khaldoun; Bachir Abdelhadi (Research in Nondestructive Evaluation, 2019)
This article presents a study of a Multi-coils circular eddy current non-destructive testing sensor for determining the fibers orientation as well as the detection of defect in multidirectional carbon fibers reinforced polymer (CFRP). The developed sensor contains 16 rectangular coils connected in series and supplied by a single-phase sinusoidal source. This sensor allows the annulations of the mechanical rotation of the conventional sensors and it permits to reduce the inspection procedure duration. The electromagnetic phenomena are calculated by using 3D finite element method (FEM) based on the electromagnetic AV-A formulation. Finally, the Multi-coils circular sensor responses are analyzed through polar diagrams of the impedance variation, where the defect is taken into consideration. A great concordance between the obtained results and those of literatures has been noticed. The provided results show that the proposed sensor allows an efficient characterization of multidirectional CFRP and detection of defects in different layers.